A Crisis in Career Development: Life Designing and Implications for Transition. (August 2019) - Wehmeyer, Michael L.; Nota, Laura; Soresi, Salvatore; Shogren, Karrie A.; Morningstar, Mary E.; Ferrari, Lea; Sgaramella, Teresa Maria; DiMaggio, Ilaria
The field of transition—and the Division on Career Development and Transition (DCDT)—was built upon a foundation established by theories of career development that emerged in the 1950s and 1960s and paved the way for the work/study movement of the 1960s and the vocational and career education for students with disabilities movement that dominated the 1970s and, eventually, the transition services movement. Today's leaders in vocational psychology and career guidance suggest that market and global economic forces associated with a postmodern world have created a crisis in career development models and methods. This article discusses the evolution of how career development has been understood, and the potential importance of a life design framework and its emphasis on career construction, rather than career development, for the future of transition services.